ENGLISH FOR SPECIFIC PURPOSES (ESP): PERSEPSI MAHASISWA DAN DOSEN PADA PROGRAM STUDI BIDANG KESEHATAN - Meisani, Diah Royani; Laely Hidayati (Journal of Practice Learning and Educational Development, 2026)
The present study was conducted to assess the efficacy of English for Specific Purposes (ESP) teaching in health-related study programs, including nursing, pharmacy, dentistry, and midwifery. By employing an explanatory sequential mixed-methods design, both students’ and teachers’ perceptions of effective English teaching were analyzed. To ensure the robust data, interviews were undertaken to support the quantitative data obtained from the questionnaire which involved 338 students and eight teachers. The findings show that not only students but also teachers agreed that feedback should be given immediately, authentic cultural-based materials, and clear instructions should be provided during the practices. Although there were different responses about the use of technology and instructional approaches, both teachers and students approved that more practices should be conducted to enhance English communication skills. Based on the results, teachers and related stakeholders are required to reconceptualize grammar and vocabulary teaching as well as to reconsider the teaching moder in order to accommodate students’ varied learning preferences. Finally, the study is expected to offer actionable insights for ESP teachers and contribute to EPS pedagogy to meet the demands of health-related English language teaching.